The Main Indicators of Rural Development in The South-East Region - Daniela – Lavinia BALASAN; Dragoș Horia BUHOCIU; Cristinel FERȚU (Communications of International Proceedings, 2022)
Agriculture is often defined and seen as a better and prosperous future for generations to come.  Starting from the idea of developing the agricultural sector, turning it into a more efficient, precise, and much more competitive pawn, it is aimed at promoting the use of new technologies but, above all, the digitization of agriculture by introducing into the system the new technologies necessary for the development of farms and companies. In this article, we looked at the need for new monitoring and control systems that would lead to reduced labor costs, improve crop yield and performance, and reduce equipment maintenance costs.  The growth of the agricultural sector through the adaptation of digitalization leads to technological innovation, not least to, creativity in transformation, animal welfare and the significant minimization of the impact on the environment.
Keywords: development; smart specialization; indicators; innovation; strategies; rural.